2020
DOI: 10.1108/nfs-03-2020-0074
|View full text |Cite
|
Sign up to set email alerts
|

Genistein supplementation improves some cardiovascular risk factors in postmenopausal women with Type 2 diabetes mellitus

Abstract: Purpose Type 2 diabetes mellitus (T2DM) is a worldwide health problem. Blood pressure (BP) and inflammation are well-established risk factors for the cardiovascular complications of T2DM. Genistein is known to improve endothelial dysfunction. The purpose of this study is to investigate the effects of genistein supplementation on BP, high-sensitive C-reactive protein (hs-CRP) and homocysteine (Hcy) levels in postmenopausal women with T2DM. Design/methodology/approach This randomized, double-blind, placebo-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…In Moreover, in a previous study, we reported that miRNA-133 and Bcl-2 downregulated in the heart of OD rats compared to the sham group (Habibi et al 2016b). Although, Braxas et al reported the improving effect of genistein on some cardiovascular risk factors in postmenopausal women with Type 2 diabetes (Braxas et al 2020), the effect of genistein on the expression of miRNA-133 and its targets genes in the heart of diabetic ovariectomized rats had not been studied. Our result showed that genistein restored diabetes-induced reduction in heart miRNA-133 and Bcl-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In Moreover, in a previous study, we reported that miRNA-133 and Bcl-2 downregulated in the heart of OD rats compared to the sham group (Habibi et al 2016b). Although, Braxas et al reported the improving effect of genistein on some cardiovascular risk factors in postmenopausal women with Type 2 diabetes (Braxas et al 2020), the effect of genistein on the expression of miRNA-133 and its targets genes in the heart of diabetic ovariectomized rats had not been studied. Our result showed that genistein restored diabetes-induced reduction in heart miRNA-133 and Bcl-2 expression.…”
Section: Discussionmentioning
confidence: 99%